Spontaneous abortions among rubber workers and congenital malformations in their offspring. - Lindbohm, M. L.; Hemminki, Kari; Kyyronen, P.; Kilpikari, I.; Vainio, Harri (Scandinavian Journal of Work, Environment & Health, 1983)
Spontaneous abortions of hospitalized women and congenital malformations were analyzed among rubber workers to investigate the possibility of an association between reproductive problems and chemical exposures in the rubber industry. Information on workers was obtained from the membership register of the Union of Rubber and Leather Workers and from the personnel register of a rubber factory. The frequencies of spontaneous abortions did not appreciably differ when the pregnancies occurred during Union membership or during employment in the factory as compared with the pregnancies occurring before or after that time. A case-referent study concerning the association between different exposures and spontaneous abortions showed that the odds ratio for factory workers exposed to rubber chemicals was increased in the footwear department. A corresponding risk was not observed in the tire department. The contradictory observations may be explained by concomitant exposure to solvents in the footwear department or by other nonoccupational factors. The possible association between congenital malformations and exposures in the rubber and leather industries was studied by the case-referent technique. No significant increase in the risk of malformations was observed in any branch of employment. However, the numbers of malformations were rather small.